Technology and the Study of Organizations: An Overview and Appraisal - Gillespie, David F.; Mileti, Dennis S. (Academy of Management Review, 1977)
“Technology” has been elusively defined, reified, treated solely as an independent variable, applied wholistically to organizations, confused with structure, crudely measured, and studied mainly in manufacturing firms. Some conceptual and methodological problems associated with the concept can be reduced by a heuristic scheme, which suggests variable theoretical statuses, different levels of analysis, application to both product and service types of organizations, and a means of clearly identifying technological effects.